Effect of inductance on the parameters of the plasma focus in a pulsed coaxial accelerator - Усеинов, Бейбут; Солодовник, Андрей; Дьяченко, Лариса; Баянова, Елена (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article considers some pedagogical and methodological aspects of the transition from the traditional system of education to teaching on the updated content of education in the framework of classroom and distance forms. The main objectives of the research were to study the effectiveness of using of criteria-based assessment, develop optimal short-term lesson plans and methodological materials for them. At the same time, the main attention is focused on the analysis of formative and summative assessment using interactive methods. As a result of the research, systematic methodological materials for physics lessons of various types were developed. The criterion of their effectiveness was a pedagogical experiment conducted in several schools in the Petropavlovsk. In the article presents diagrams of the results of determining the effectiveness of the new developed materials using interactive teaching methods during the criterion assessment of student success. During the pedagogical experiment the study of physics in high grades of the secondary school occurred in synchronous and asynchronous formats of distance learning. The results of the pedagogical experiment allow to speak about the positive influence of these methods on the progress of students.